The Implementation of Islamic Penal Law in Brunei Darussalam and International Society - Anton Minardi; Rini Afriantari; Maesuroh Maesuroh (FISIP UIN SGD Bandung, 2021)
This article discusses the application of the shari'a penal code in Brunei Darussalam, in the Brunei institutionalization called Perintah Kanun Jenayah Syariah. The research in this discussion using qualitative methods with descriptive analysis techniques. Brunei Darussalam inaugurated the punishment of the shari'a crime on May 1, 2014, and applied in 3 stages; the stages imposed the criminal penalty in the level of violations and sanctions from mild to severe. The reaction o fthe international community can not be avoided because the punishment concerns Human Rights, which became a hot issue after the cold war. The response of oral and written censure in electronic media and mass media has harmed the government and the image of the Brunei sultanate family. Brunei state has carried out various actions so that the condition will not cause any protracted defect and sharia law will be implemented.